Fraction Triangle Cards (FTC) game as learning media for multiplying fractions in fifth-grade elementary school - Trimurtini, Trimurtini; Astuti, Fatma Dwi; Nugraheni, Nursiwi (Department of Mathematics, Universitas Negeri Semarang, 2019)
Learning media can help in improving the students’ skills, so they can achieve the learning objectives effectively. This research is development research that aims to create learning media that is feasible and valid. This research uses concrete objects in the form of cards for multiplying fraction materials in grade 5 Public Primary School of Tambakaji 04 Semarang. The research was conducted by using Sugiyono’s development method. The techniques of data collection conducted in this study were (1) questionnaire, to evaluate the media validity, obtained through validation by the validators, (2) test, to measure the media effectiveness obtained through students’ learning outcomes. The results show that the average score of media validity is 90%, and media effectiveness from students’ learning outcomes is 0.4. Therefore, this learning media is practical and feasible so that it can be used in multiplying fractions learning in the fifth grade of elementary school.